Juridical Review of Absentee Ownership of Agricultural Land Rights through Inheritance Based on Basic Agrarian Law - Taufiq, Luthfi Nurahmad; Sri Darmadi, Nanang (TABELLIUS: Journal of Law, 2023)
Absentee land ownership can create legal uncertainty and risks for parties involved in using the land, such as tenants, cultivators, or parties who have other interests in the land. Thus, this research aims to determine and analyze the legal status of heritage objects in the form of absentee land, and legal protection for heirs who receive rights to absentee land. The research method used is normative juridical with a statutory approach and a conceptual approach. The type of data used is secondary data sourced from primary and secondary legal materials. Data collection method using literature study. The data analysis method uses perspective analysis. The results of the research conclude that the legal status of the inheritance object in the form of absentee land, if a legal event occurs which causes the transfer of ownership rights to the land is an inheritance process. This inheritance event causes absentee ownership of land. According to the law, absentee land ownership is clearly prohibited, but what is prohibited is absentee land ownership, isn't it? Therefore, when the heir is truly a legal heir according to law, the heir can receive the rights to the inheritance given by the heir, thus the heir can still receive the inheritance in the form of agricultural land even though the heir lives in outside the sub-district that borders the location of the land. Legal protection for heirs who have rights to absentee land according to the law is that when the heirs can cultivate and work on the agricultural land efficiently without using extortion methods, then the heirs can still have rights to the land by moving to the location of the agricultural land that the heir owns. Keywords: Absentee; Heirs; Inheritance; Land; Protection.